ANALISA PENGARUH PEMBIAYAAN AKAD MUROBAHAH (Jual-Beli) TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) PERIODE 2013-2015 (Studi Kasus Pembiayaan UMKM Di BMT Sunan Pandanaran Sleman Yogyakarta) - Mochamad Mansur (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
The Murobahah contract is a sale and purchase with the original price plus profit after an agreement between the seller and the buyer are allowed because it contains an element of help. Murabaha's program is very helpful for customers of BMT Sunan Pandanaran based on research results from 900 customers and taken samples of 100 customers. BMT Sunan Pandanaran who received financing experienced an increase in income which was indirectly able to raise the Human Development Index for BMT customers. The results showed that from 100 samples taken with different work backgrounds they on average experienced an increase in income of 300,000 to 4,000,000 after taking financing or with a murobahah contract, seen from the consumption of daily needs after becoming a BMT 94 customer. % said that the needs of 4 healthy 5 were fulfilled, as well as funding for school children 79% said school fees for their children could be met through BMT financing.